Pengaruh Faktor Harga Dan Merek Terhadap Minat Beli Model Desain Sepatu Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta - Radhityo, Lukman, Drs. Kusdiyanto, M.Si (2015)
The purpose of this research is to know the price of buying interest has an influence on the design model shoes on students of the Faculty of Economics and Business, University of Muhammadiyah Surakarta, knowing the brand has an influence on buying interest in shoe design students of the Faculty of Economics and Business, University of Muhammadiyah Surakarta. The population in this study is on mahasiswaFakultas Economics and Business Universitas Muhammadiyah Surakarta and samples used in this study was taken a sample of 100 respondents. Analysis of data using multiple linear regression test, t test, F test and the coefficient of determination (R2). Based on the results of the t test analysis of price variables known to have a significant impact on the design of the shoe buying interest. Variable brand has a significant influence on the buying interest model of shoe design. Based on these results that the most dominant factor in influencing consumer buying interest is the brand. This is because the brand has a factor of 6.728 tcalculate as big as value compared to other variable is the price factor of 5.793. The test results are known Fcalculate> Ftable (84.664> 4.00), then Ho is rejected, Means jointly price variable (X1) and brand (X2) effect together towards buying interest shoes. Result design model coefficient of determination ( R2) obtained adjusted R-square (R2) obtained at 0.628, meaning variation changes the variable interest in buying shoe designs can be explained by the price variable (X1) and brand (X2) has positive influence on buying interest at 62.8%. While the rest of 37.2% is explained by other variables outside the model.